2019
DOI: 10.1007/s00256-019-3168-9
|View full text |Cite
|
Sign up to set email alerts
|

The peroneus longus muscle and tendon: a review of its anatomy and pathology

Abstract: This article will review the anatomy and common pathologies affecting the peroneus longus muscle and tendon. The anatomy of the peroneus longus is complex and its long course can result in symptomatology referable to the lower leg, ankle, hindfoot, and plantar foot. Proximally, the peroneus longus muscle lies within the lateral compartment of the lower leg with its distal myotendinous junction arising just above the level of the ankle. The distal peroneus longus tendon has a long course and makes two sharp tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 61 publications
0
15
0
8
Order By: Relevance
“…Due to its insertion on the medial aspect of the foot and course down the lateral part of the leg, muscle contraction lifts the foot upward (plantar flexion) and outward (eversion). This movement is critical to eversion of the foot and can be injured commonly from forced inversion and dorsiflexion of the ankle in the setting of trauma 21 . In addition, Kokubo et al have previously shown that the traction on the m. peroneus longus tendon decreased the stiffness of the foot 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its insertion on the medial aspect of the foot and course down the lateral part of the leg, muscle contraction lifts the foot upward (plantar flexion) and outward (eversion). This movement is critical to eversion of the foot and can be injured commonly from forced inversion and dorsiflexion of the ankle in the setting of trauma 21 . In addition, Kokubo et al have previously shown that the traction on the m. peroneus longus tendon decreased the stiffness of the foot 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The tendon of m. tibialis anterior is attached to the medial cuneiform bone and the base of the 1st metatarsal bone, due to which this muscle is involved in maintaining the medial longitudinal arch of the foot 20 . M. peroneus longus affects both the longitudinal and transverse arches of the foot 21 , 22 , since it follows the outer surface of the calcaneus and passes to the sole, where it obliquely crosses the foot and attaches to the tuberosity of the 1st and the base of the 2nd metatarsal bones.
Figure 4 ( a ) Graphic image of places of measurement of the stiffness of soft tissues.
…”
Section: Methodsmentioning
confidence: 99%
“…The lateral tendon group is represented by peroneus longus (PL) and brevis tendons. Comprehensive analysis of the PL should include its entire course from the lower leg to the plantar foot at its insertion [44,45]. Evaluation of the distal PL tendon is particularly important.…”
Section: Lateral Tendonsmentioning
confidence: 99%
“…Evaluation of the distal PL tendon is particularly important. Its dominant insertion on the plantar base of the first metatarsal and medial cuneiform and additional variable tendinous slips act to stabilise the first tarsometatarsal joint and the Lisfranc joint as well as support the tarsometatarsal arch [45][46][47]. At the retromalleolar groove of the fibula, the peroneus brevis (PB) tendon is normally located anteromedially to the PL tendon ( Figure 9) [48].…”
Section: Lateral Tendonsmentioning
confidence: 99%
See 1 more Smart Citation